Engineered ceramics : current status and future prospects - Ohji, T. (Tatsuki); Singh, M. (Mrityunjay) (Wiley, 2015)
In this book project, all the American Ceramic Society's Engineering Ceramics Division Mueller and Bridge Building Award Winners, the ICACC Plenary Speakers and the past Engineering Ceramics Division Chairs have been invited to write book chapters on a topic that is compatible with their technical interests and consistent with the scope of the book, which is to focus on the current status and future prospects of various technical topics related to engineering ceramics, advanced ceramics and composite materials.